Non-intubated Thoracic Surgery: Wedge Resections for Peripheral Pulmonary Nodules - Ambrogi, Vincenzo; Patirelis, Alexandro; Tajè, Riccardo (Frontiers in Surgery, 2022)
The feasibility of performing pulmonary resections of peripheral lung nodules has been one of the main objectives of non-intubated thoracic surgery. The aim was to obtain histological characterization and extend a radical intended treatment to oncological patients unfit for general anesthesia or anatomic pulmonary resections. There is mounting evidence for the role of wedge resection in early-stage lung cancer treatment, especially for frail patients unfit for general anesthesia and anatomic resections with nodules, demonstrating a non-aggressive biological behavior. General anesthesia with single lung ventilation has been associated with a higher risk of ventilator-induced barotrauma and volotrauma as well as atelectasis in both the dependent and non-dependent lungs. Nonetheless, general anesthesia has been shown to impair the host immune system, eventually favoring both tumoral relapses and post-operative complications. Thus, non-intubated wedge resection seems to definitely balance tolerability with oncological radicality in highly selected patients. Nonetheless, differently from other non-surgical techniques, non-intubated wedge resection allows for histological characterization and possible oncological targeted treatment. For these reasons, non-intubated wedge resection is a fundamental skill in the core training of a thoracic surgeon. Main indications, surgical tips, and post-operative management strategies are hereafter presented. Non-intubated wedge resection is one of the new frontiers in minimal invasive management of patients with lung cancer and may become a standard in the armamentarium of a thoracic surgeon. Appropriate patient selection and VATS expertise are crucial to obtaining good results.